In vitrodetection of bacterial contamination in platelet concentrates by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry: a preliminary study. Issue 11 (November 2017) - Chetouane, Yasmine; Dubourg, Gregory; Gallian, Pierre; Delerce, Jeremy; Levasseur, Anthony; Flaudrops, Christophe; Chabrière, Eric; Chiaroni, Jacques; Raoult, Didier; Camoin‐Jau, Laurence
Abstract : Purpose. : Platelet concentrates are at risk of transfusion‐related sepsis. The microbial detection methods currently available have reached their limits, as they do not completely prevent transfusion‐related bacterial contamination. The aim of this study was to develop a new strategy to detect the risk of platelet transfusion‐related bacterial contamination using matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS). Methodology. : In vitro, platelet concentrates were seeded with known concentrations of bacterial strains. Protein mass profiles were acquired by using a Microflex MALDI‐TOF instrument. Dedicated 'Platelet' software was used as a spectrum subtraction tool to reveal specific peaks caused by the presence of pathogens in samples. Results. : The MALDI‐TOF spectra of platelets were characterized and the reproducibility over time, regardless of the blood donor, was demonstrated with a positive predictive value of 100%. In addition, the negative predictive value of the total number of specific peaks to predict contamination was 100%. Conclusion. : Detecting bacteria in platelet concentrates using the MALDI‐TOF approach and analysing spectra with the Platelet software present the advantage of combining the precocity of results and sufficient sensitivity (10 c.f.u. ml −1 ). Further research will be conducted to compare this novel method with the current conventional method in order to validate our results, the objective being to reduce the risk of platelet transfusion‐related bacterial contamination.